Collateral effects of the SARS-CoV-2 pandemic on oncologic surgery in Bavaria - Thomas Dienemann (BMC, 2021)
Abstract Background The ongoing SARS-COV-2 pandemic has severe implications for people and healthcare systems everywhere. In Germany, worry about the consequences of the pandemic led to the deferral of non-emergency surgeries. Tumor surgery accounts for a large volume in the field of visceral surgery and cannot be considered purely elective. It is not known how the SARS-COV-2 pandemic has changed the surgical volume in tumor patients. Methods Retrospective analysis of the amount of oncological surgeries in three academic visceral surgery departments in Bavaria, Germany, in 2020. Procedures were split into subgroups: Upper Gastrointestinal (Upper GI), Colorectal, Hepato-Pancreato-Biliary (HPB), Peritoneal and Endocrine. Procedures in 2020 were compared to a reference period from January 1st, 2017 to December 31st 2019. Surgical volume was graphically merged with SARS-COV-2 incidence and the number of occupied ICU beds. Results Surgical volume decreased by 7.6% from an average of 924 oncologic surgeries from 2017 to 2019 to 854 in 2020. The decline was temporally associated with the incidence of infections and ICU capacity. Surgical volume did not uniformly increase to pre-pandemic levels in the months following the first pandemic wave with lower SARS-COV-2 incidence and varied according to local incidence levels. The decline was most pronounced in colorectal surgery where procedures declined on average by 26% following the beginning of the pandemic situation. Conclusion The comparison with pre-pandemic years showed a decline in oncologic surgeries in 2020, which could have an impact on lost life years in non-COVID-19 patients. This decline was very different in subgroups which could not be solely explained by the pandemic.